Green signals? Assessing price dynamics in the European renewable energy certificate marketMendeley Data - Johannes Bösch (Energy Strategy Reviews)
Guarantees of Origin (GOs) certificates were introduced by European governments to reduce information asymmetry in electricity markets. By providing verified information on the origin of electricity, GOs enable consumers to credibly identify and demand electricity from renewable sources. This consumer-driven demand can create price signals that can incentivize additional renewable investment. However, academic literature and market participants have argued that the geographical and temporal decoupling of GOs from physical electricity flows limits the market's effectiveness in driving additional renewable capacity. This paper analyzes whether these critiques are empirically re-flected in historical price dynamics in the European GO market. It leverages a novel data set of real-world price data between 2016 and 2023. It conducts a granular analysis of price premia between GO technologies over different periods and explores GO price responsiveness to energy market fluctuations. Results demonstrate unstable price differences across technologies and a significant lag in GO price responses to changes in carbon demand. These findings provide empirical support for the claim that current GO price signals are weakly aligned with the locational and temporal value of green electricity. Thereby, this study seeks to provide an empirical basis to guide strategic energy policy discussions on implementing more granular matching requirements for green certificates.